Effect of chlorhexidine, honey and Propolis on Streptococcus mutans Counts: in vitro Study - Abdulrhman Alkhaled (University Library System, University of Pittsburgh, 2021)
Objective: .Streptococcus mutans is considered one of the bacteria that causes necrosis, as it metabolism sugar to obtain energy, producing an acidic environment and causing depression in the enamel surface, which causes the dissolution of the calcium molecule, a problem of cavited in the tooth; so the aim of the research is to evaluate the effect of mouthwashes chlorhexidine 0.12% - honey 50% - propolis 5% on Streptococcus mutans in children.